Preparing to Teach Democracy: Student Teachers’ Perceptions of the ‘Democracy Cake’ as a Set of Teaching Materials in Social Science Education - Nora Elise Hesby Mathé (Journal of Social Science Education, 2020)
Purpose: Few studies have examined student teachers’ perceptions of teaching materials on democracy. For the purpose of addressing how teacher education in social science might contribute to student teachers’ qualifications for teaching democracy, this study investigated student teachers’ perceptions of the ‘Democracy Cake’ as a set of teaching materials for teaching democracy in social science education.